VARIASI STRUKTUR ANATOMI DAUN DARI BEBERAPA JENIS TUMBUHAN DIKOTIL SEBAGAI RANCANGAN BOOKLET PADA PEMBELAJARAN BIOLOGI SMA - Chrisdayanti Br Simanjuntak; Imam Mahadi; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
This research was conducted to determine the variation of leaf anatomical structure of dicotyledonous plants and to produce a design of booklet teaching materials in class XI Biology learning on plant tissue structure and function. This research was conducted in the biology laboratory of the Faculty of Mathematics and Natural Sciences, Riau University using the paraffin method for the preparation of preserved preparations and the design of booklets was carried out at the biology education campus, FKIP UNRI. This research was carried out in 2 stages, the first stage was to analyze variations in the anatomical structure of leaves. dicots and the second stage is the design of booklet teaching materials from the research results. The results of the qualitative study of the anatomical structure of water spinach leaves (Ipomoe aquatica Forsk), Lotus (Nympahea alba), green betel (Piper betle) and Hibiscus (Hibiscus rosasinensis) have differences and similarities in qualitative characters, namely different epidermis shapes, consists of 1 epidermal cell, stomata located on the upper surface and lower surface of the epidermis, on the leaves of water spinach (Ipomoe aquatica Forsk) and Lotus (Nympahea alba), there are different trichomes. Based on the potential analysis of the research results, it can be used as a design for biology learning booklet on the material structure and function of plant tissue in class XI SMA at KD 3.3 and KD 4.3.Key Words: anatomical structure, leaves, dicotyledonous plants, booklet